2011
DOI: 10.1128/jcm.00261-11
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Commercial Toxigenic Clostridium difficile PCR Resulting in Improved Economy and Workflow Efficiency

Abstract: Expense inherent to molecular diagnostics may prevent laboratories from utilizing real-time PCR for Clostridium difficile infection. Frozen master mix and overnight aliquot modifications of the BD GeneOhm Cdiff assay failed to impact performance indices compared to the package insert protocol (P > 0.31), provided accurate results, and decreased reagent expenditure.Traditional laboratory methods detecting toxigenic Clostridium difficile to confirm Clostridium difficile infection (CDI) suffer from deficiencies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The use of frozen master mix reduces hands-on time by 15%, even if it is not recommended by the manufacturer. Sensitivity, specificity and inhibitor rates are similar with frozen or freshly reconstituted master mix [28].…”
Section: Bd Geneohm Cdiffmentioning
confidence: 67%
“…The use of frozen master mix reduces hands-on time by 15%, even if it is not recommended by the manufacturer. Sensitivity, specificity and inhibitor rates are similar with frozen or freshly reconstituted master mix [28].…”
Section: Bd Geneohm Cdiffmentioning
confidence: 67%
“…However, lyophilization is a multistep process requiring specialized equipment. An alternative approach to the reduction of molecular assay setup times is the utilization of preassembled frozen master mixes [Kofler and Klausegger, 1999;West and Sawyer, 2006;Munson et al, 2010Munson et al, , 2011]. Previous reports have described the successful ability of preassembled conventional and real-time PCR master mixes to maintain performance following freezing [Kofler and Klausegger, 1999;West and Sawyer, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical microbiology market, this real-time polymerase chain reaction (rtPCR) assay was followed by several other BD GeneOhm™ tests, initially developed by our group, for the rapid diagnostics of hospital-acquired infections associated to methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and Clostridium difficile . It has been shown that these tests have saved lives, decreased the spread of these infections, and reduced healthcare costs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Personalized Medicine For Infectious Diseases?mentioning
confidence: 99%